PSIKOLOGI ORGANISASI DAN PENGARUHNYA TERHADAP BUDAYA KERJA DI MTSN 1 SUMEDANG - Maulana, Teguh Iqbal; Nugraha, Mulyawan Safwandy (STKIP Pesisir Selatan, 2026)
Objective: This study examines the influence of organizational psychology on work culture at MTsN 1 Sumedang, focusing on motivation, communication, conflict management, and leadership within an Islamic educational context. Methods: A qualitative case study approach was employed, using purposive sampling. Data were collected through in-depth interviews with a senior teacher (Ibu Eva), participant observation, and documentation analysis, then analyzed using Miles, Huberman, and Saldaña’s interactive model. Results: The findings reveal that although the term